Cytokine responses to LPS in reprogrammed monocytes are associated with the transcription factor PU.1. Issue 4 (13th March 2022) - Tuerxun, Kedeye; Midtbö, Kristine; Särndahl, Eva; Vorontsov, Egor; Karlsson, Roger; Persson, Alexander; Kruse, Robert; Eklund, Daniel; ,
Abstract: Myeloid‐derived suppressor cells (MDSCs) are functionally immunosuppressive cells that arise and expand during extensive inflammatory conditions by increased hematopoietic output or reprogramming of immune cells. In sepsis, an increase of circulating MDSCs is associated with adverse outcomes, but unique traits that can be used to identify increased activity of MDSCs are lacking. By using endotoxin tolerance as a model of sepsis‐induced monocytic MDSCs (M‐MDSC‐like cells), this study aims to identify the mediator and transcriptional regulator profile associated with M‐MDSC activity. After analyzing 180 inflammation‐associated proteins, a profile of differentially expressed cytokines was found in M‐MDSC‐like cells versus normal monocytes stimulated with LPS. These cytokines were associated with 5 candidate transcription factors, where particularly PU.1 showed differential expression on both transcriptional and protein levels in M‐MDSC‐like cells. Furthermore, inhibition of PU.1 led to increased production of CXCL5 and CCL8 in M‐MDSC‐like cells indicating its role in regulating the ability of M‐MDSC‐like cells to recruit other immune cells. Taken together, the study identifies a unique profile in the pattern of immune mediators defining M‐MDSC activity upon LPS stimulation, which offers a functional link to their contribution to immunosuppression. Graphical Abstract: Differential cytokine response in endotoxin induced M‐MDSC‐like cells and their associated regulators. Summary sentence: Differential cytokine response in endotoxin induced M‐MDSC‐like cells and their associated regulators.